Skrining Senyawa Antibakteri dari Beberapa Jenis Rumput Laut Coklat (Phaeophyceae) dari Pantai Drini, Daerah Istimewa Yogyakarta - Sidharta, Boy R.; Atmodjo, P. Kianto; Mursyanti, E. (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2008)
This present research was trying to determine the antibacterial compounds from several brown seaweeds from Drini beach. Previous studies have shown that several seaweeds from this beach were proved to have antibacterial activities. Therefore, it needs to be studied whether the extracts of several brown seaweeds utilizing three (3) kinds of extraction solutions such as aquadest, ethanol, and hexane, will also show antibacterial activities. The three solutions were chosen based on the difference of polarization activities. Research design utilized was randomized complete block design and the data compiled was treated by Anova and followed with Duncan’s Multiple Range Test (DMRT) with degree of confidence 95%. Microbes utilized in this research were Escherichia coli and Bacillus subtilis, that were common pathogenic bacteria known to human and animals. The research found six (6) species of brown seaweed during the research period, i.e. Sargassum dotyi, S. ohnoi, S. abbottiae, S. bataanense, Caulerpa prolifera, and Laurencia papillosa. This present research also revealed that ethanol was the best extraction solution to extract the secondary metabolite from the brown seaweeds found. The best antibacterial activities was shown by S. dotyi extract’s to inhibit the two (2) microbes used in the research compared to other seaweed extracts. However, this result was still low and significantly different compare to pure antibiotics utilized, i.e. penicillin and streptomycin.